Short physical performance battery is not associated with falls and injurious falls in older persons: longitudinal data of the SCOPE project - Freiberger, Ellen; Fabbietti, Paolo; Corsonello, Andrea; Lattanzio, Fabrizia; Sieber, Cornel; Tap, Lisanne; Mattace-Raso, Francesco; Ärnlöv, Johan; Carlsson, Axel C.; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Moreno-Gonzalez, Rafael; et al. (European Geriatric Medicine, 2024)
Introduction: Falls and fall-related injuries in older persons are a major public health problem. Our objective was to study the predictive value of the Short Physical Performance Battery (SPPB) in the cohort of the SCOPE project on falls, injurious falls, and possible difference of prediction between indoors and outdoors falls. Methods: For this sub-study of the SCOPE project participants reporting no falls at baseline, and survey data on falls at the 12-month and 24-month follow-up were included. Participant´s characteristics were assessed during the baseline interview and medical examinations. Falls as well as injurious falls and fall circumstances were obtained self-reported. SPPB and its association with fallers vs. no fallers at 12 and at 24 months were studied with logistic regression models. Results: The 1198 participants had a median age of 79 years (77–82), and a median SPPB of 10 (8–11), with a 52.5% of female. A total of 227 and 277 falls (12- and 24- month visits, respectively) were reported. In the crude model, the SPPB sum scores (p < 0.001) as well as most single item scores were significant different between fallers and non-fallers over time. However, the association was attenuated in models adjusted for age, sex, marital status, number of medications, quality of life, handgrip strength, and muscle mass [e.g., 12 months; OR 0.94 (0.87–1.02)]. While SPPB fails to differentiate between injurious and non-injurious falls (p = 0.48), a lower SPPB score was associated with falls at home (p < 0.01) after 24 months. Conclusion: SBPP was not able to significantly predict the risk of falling as well as experiencing an injurious fall. Trial registration: This study was registered prospectively on 25th February 2016 at clinicaltrials.gov (NCT02691546).
CRIS-Team Scopus Importer:2024-03-08
Keywords: Falls; Injurious falls; Longitudinal study; Physical function; Short physical performance battery